The Relationship between Tax Law and Other Laws: A Review of Problems in Tax Collection - Ending Solehudin; Atisa; Della Agustina; Jihan Syahirah Lubis; Rahma Seliati Br Sitorus (ISNU Sumatera Utara, 2024)
Tax law, a collection of regulations governing the relationship between the government as tax collector and the people as taxpayers, defines taxes as mandatory contributions to the state owed by individuals or entities that are coercive under the law, without receiving any direct compensation and are used for state purposes for the greatest prosperity of the people. Tax compliance is a major issue that requires greater attention in the era of private system evaluation. Several key factors affecting tax collection are taxpayer trust in tax institutions, complex regulations, low public awareness of taxes, and tax administration. It is hoped that improvements in organizations, human resources (HR), information technology, business processes, and tax laws and regulations will help overcome tax administration problems and increase taxpayer compliance.